ANALISIS TINGKAT KEKOTAAN DI SEPANJANG JALAN NASIONAL KABUPATEN DHARMASRAYA - Zikra, Albi - (STKIP PGRI Sumbar, 2014)
This study aimed to describe the urban level along the national road Dharmasraya seenfrom overcrowding, non-agricultural households and access urban facilities.The research is a descriptive survey method with the aim to explain the variables studiedwith the final result of the economic structure of the known population in agriculture and nonagricultureas well as the level of the urban area along the national road Dharmasraya. The objectof research is the area along the National Road Dharmasraya were divided into 5 blocks, namelyBlock I (District Boundaries to Batang Hari River), block II (Batang Hari River - Simpang EmpatSikabau), Block III (Simpang Empat Sikabau - Gunung Medan Simpang Empat) Block IV(Gunung Medan Simpang Empat - Simpang Empat Koto Baru) and Block V (Simpang EmpatKoto Baru - limit Jambi).The study found: 1) the urban level along the national road in the district based onpopulation density Dharmasraya divided into two parts, namely: population density <500inhabitants / km consists of 4 blocks and population density> 500 inhabitants / km consists of 1block, 2) the urban level along the national road in the district based on the percentage ofhouseholds Dharmasraya nonagricultural divided into two parts, namely skor5 and score 6. score 5is the non-farm households that are within the range of scores from 20.0 to 29.9% the area of theblock II and scores 6 is a non-agricultural households that are within the range of scores from 30.0to 49.9% the area of the block I, II, IV and V, 3) the urban rate along the national road inDharmasraya based access to urban facilities, the range of scores obtained 4 - 7, the lowest accessto the block area and the third highest in the block I, IV and V, and 4) the classification of the areain the district Dharmasraya Along the national road based on the block, the entire region based onthe block including urban areas with a score range between 11-14